Phytochemical Constituents and Biological Activity of Wild and Cultivated Rosmarinus officinalis Hydroalcoholic Extracts - Rosaria Francolino; Mara Martino; Lucia Caputo; Giuseppe Amato; Giuseppina Chianese; Ernesto Gargiulo; Carmen Formisano; Benedetta Romano; Giuseppe Ercolano; Angela Ianaro; Laura De Martino; Vincenzo De Feo (MDPI AG, 2023)
Rosmarinus officinalis L. is an aromatic evergreen plant from the Lamiaceae family. The purpose of this study was to compare the chemical profile and bioactivities of hydroalcoholic extracts derived from wild and cultivated R. officinalis. The chemical composition of the extracts was evaluated via LC-MS analysis, which revealed the presence of a wide range of phenolic compounds, including flavonoids, phenolic and terpenes. Both extracts showed a similar interesting antioxidant activity, probably related to their content of phenol and flavonoids. The analysis of anti-acetylcholinesterase (AChE), anti-butyrylcholinesterase (BChE), and anti-α-amylase activities showed analogous inhibition, except for AChE, in which the wild type was more active than the cultivated one. Finally, in vitro studies were performed using the J774A.1 murine macrophage cell line, to characterize the anti-inflammatory and the antioxidant effects of the extracts. As expected, pretreatment with the extracts significantly reduced the production proinflammatory cytokines and ROS through modulation of the nitric oxide pathway and the mitochondrial activity. Importantly, it is observed that the anti-inflammatory effect of the extracts was explicated through the inhibition of NF-kB and its downstream mediator COX-2. Collectively, these results demonstrated that these extracts could represent a starting point for developing novel therapeutic strategies for the treatment of inflammation-based diseases. Moreover, since no significant changes were observed in terms of composition and activity, both wild and cultivated R. officinalis extracts can be recommended for food and pharmaceutical purposes.